“Improving the Quality of the Salt-Tolerant Rice Lines by Molecular Breeding” - Tran Trung; Khuat Huu Trung; Nguyen Thi Loan; Nguyen Thi Thuy Anh; Hoang Thi Loan; Nguyen Hoang Long; Nguyen Thai Duong; La Hoang Anh; Tran Dang Xuan; Phan Phuoc Minh Hiep; Tran Dang Khanh (My University, 2019)
“Improving the Quality of the Salt-Tolerant Rice Lines by Molecular Breeding”
Keywords: Lúa chịu mặn; Chọn tạo giống phân tử; Cải thiện chất lượng